Screening for refractive error among high school children - Dr.S. ARUNA, M.Sc(N)., Ph.D.,RN, RM,; Mrs.THENMOZHI.P, M.Sc(N), RN, RM, (International Journal of Pharma and Bio Sciences, 2016)
There’s an alarming increase in the number of children suffering from eye problems these days. Diagnosing and treating them early are critical to maintaining a child’s eye health. Refractive errors constitute a sizeable proportion of any large eye out patient department in our country. The overall incidence has been reported to vary between 21% and 25% of the patients attending eye out patient department in India. The aim of the study was to screen the refractive error among school children. The research design adopted for this study was non-experimental cross sectional. The study was conducted at selected schools in Kancheepuram District with 1169 samples by using a quota sampling technique. The sample of the study was the school children who are studying VI, VII, VIII& XI standard with the age group between 11 to 14 years of both male and female children. Visual acuity was assessed for each eye by using Snellen chart, ophthalmoscopic and fundoscopic examination. There were around 1169 students were screened from selected schools. Out of 1169 students 279 students have refractive error. Out of 279 students 163 students were male and 116 students were female. The number of refractive errors was higher among IX standard students. The incidence of refractive error among school children was high. Many of the children are undiagnosed due to ignorance by the parents and lack of awareness about the refractive error. Vision screening should be done periodically in school as a part of school health programme.